Implementing Genomic Clinical Decision Support for Drug‐Based Precision Medicine. (March 2017) - Freimuth, RR; Formea, CM; Hoffman, JM; Matey, E; Peterson, JF; Boyce, RD
Abstract : The explosive growth of patient‐specific genomic information relevant to drug therapy will continue to be a defining characteristic of biomedical research. To implement drug‐based personalized medicine (PM) for patients, clinicians need actionable information incorporated into electronic health records (EHRs). New clinical decision support (CDS) methods and informatics infrastructure are required in order to comprehensively integrate, interpret, deliver, and apply the full range of genomic data for each patient.1